Nilai-Nilai Kebermaknaan Hidup Mama Sempur (Kh. Tubagus Ahmad Bakri) Dalam Naskah Cempakadilaga - Ida Afidah; Titin Nurhayati Ma’mun; I. Syarief Hidayat; Elis Suryani (Syifa al-Qulub, 2020)
This study is aimed to find values of the meaning of life that written by Ajengan Mama Sempur in the Book of Campaka Dilaga. This study used a qualitative method with a literature study approach. The result of this study was found that the meaning of life of a Muslim can be found through the five values that exist in the five clauses and faidah’s chapters, namely: First clause, discussing the urge to work / work for Muslims. The second clause, discussing the prohibition of doing business or doing work that is prohibited by Islam. The third clause, discussing the obligation to establish good relations with neighbors. The fourth clause, discussing the obligation of Muslims to serve and obey the legitimate government. The fifth clause, discussing the rules of ushul fiqh preventing harm is better than bringing benefit. The conclusion of this research is that the meaning of life can be found in the Sufistic values of Mama Sempur and her thoughts about the value of community life in accordance with the current conditions so as to give birth to good character.